Solar/metal activation of persulfate in homogeneous processes for simultaneous degradation of antibiotic and dye pollutants - Moradi, Mehrdad; Saien, Javad (Journal of photochemistry and photobiology. A, Chemistry., 2025)
[Display omitted] •Simultaneous degradation of antibiotic and dye pollutants with Solar/PS/Fe2+/Cu2 + processes.•Mild operating conditions and utilizing low dosages of persulfate oxidant and metal reagents.•High performance thin-layer flow solar photo-reactor in handling the process.•Identifying intermediates and illustrating degradation pathways based on LC-MS analysis.•High toxicity level reduction after treatment based on an standard analysis. Antibiotics are widely used in human, veterinary and aquaculture for disease control. Edible dyes, on the other hand, are often used in the manufacture of drugs. Both of these can pollute the environment when concentrated in water. In this study, solar-activation of persulfate (PS) in aqueous media was employed for the simultaneous degradation of penicillin-G (PG) drug and rhodamine-B (RhB) dye. Experiments were conducted in a thin-layer flow photo-reactor, irradiated with a standard solar light simulator. Under mild optimum conditions of pH 6.9, PS concentration of 225 mg/L and a reaction time of 70 min, 79.1 % and 90.1 % degradations were achieved for PG and RhB pollutants, respectively. Adding only 0.42 mg/L of Fe2+ and 0.47 mg/L of Cu2 + ions, improved degradation and COD reduction to respectively, 99.7 % and 85.6 %. Alternative relevant homogenous processes were examined and the interference of different coexisting water matrices was studied. Further, contribution of reactive oxygen species was determined and the relevant eleven intermediates were identified based on LC-MS analysis followed by evaluating the product toxicity level with the antibiogram test. This study highlights using the Solar/PS/Fe2+/Cu2 + homogeneous process for the treatment of pharmaceutical and dye wastewaters.